Training and Development as Correlate of Effectiveness and Loyalty of Employees: A Case of Transmission Company of Nigeria - Olonade, Zaccheaus Olufunminiyi; Omotoye, Oluwatobi Oyewumi (PYC Nepal Journal of Management, 2021)
The study aims to examine the impact of training and development on effectiveness and loyalty among workers of Transmission Company of Nigeria, Osogbo, Osun State. The study adopted a descriptive survey research design. The study collected data through a structured questionnaire which contained three sections for demographic variables, Employee Training and Development Scale, and Employees' Effectiveness and Loyalty Scale respectively. 80 respondents were selected through the use of random sampling techniques across the establishment. Descriptive and inferential statistics were used to analyses the data. The hypotheses were tested with Pearson Product Moment Correlation and regression analysis. Hypothesis one revealed a positive correlation between employee training & development and employees’ effectiveness. The result of the second hypothesis indicated a positive correlation between training & development and employees loyalty. The study recommended regular intensive training to achieve the company's objectives through staff effectiveness. Management should also focus on innovative developmental programmes and policies for employees to be more loyal.